EYE TRACKING AND VOICE CONTROL FOR COMPUTER APPLICATION - Vivek, Pindikanti; Singh, Akshay; Amutha, A.L. (International Journal of Psychosocial Rehabilitation, 2020)
The concept of digital image processing and speech recognition can be used for tracking the eye movement which can help in controlling the mouse on the screen and performing the specified function using voice commands. To track eye a macro lens camera is used, which will be placed close in front of the user’s eye. A human eye has 3 visible regions – Sclera, Iris and Pupil. Sclera is white in color, color of Iris varies from person to person, but Pupil is black in color. This allows us to track the pupil’s movement on the eye. The second camera will be positioned on the user’s head which will track the screen edges and determine the distance between user and screen, it will also track the head rotation to determine the exact cursor position. The pupil’s position can be then mapped on to the screen so that the mouse moves relative to the eye. The mapping is done by resizing the screen frame to fit the eye frame and tracking the center of the eye relative to the screen edges. After finding the cursor coordinates it is important to remove noise. Noise can be in the form of non-continuous cursor movement or cursor moving back and forth even if the user is idle. The voice recognition system will process the user’s voice and converts it into text which can be used as commands for computer operation. These operations involve clicking, double-clicking, right-clicking, typing, etc. The main idea of this project is to minimize the number of input devices and increase the ease of human computer interaction. It will be useful for people who are suffering from amputation or who want an ergonomic work space, as it minimizes the use of hands for interacting with the computer.